9B.01: CLINICAL SIGNIFICANCE OF CONTRALATERAL ADRENAL SUPPRESSION DURING ADRENAL VEIN SAMPLING IN PRIMARY ALDOSTERONISM. (June 2015) - Monticone, S.; Satoh, F.; Viola, A.; Fischer, E.; Vonend, O.; Bernini, G.; Quinkler, M.; Ronconi, V.; Morimoto, R.; Kudo, M.; Degenhart, C.; Gao, X.; et al.
Abstract : Objective: Adrenal vein sampling (AVS) is recognized by Endocrine Society guidelines as the only reliable mean to distinguish between aldosterone producing adenomas and bilateral adrenal hyperplasia, the two most common subtypes of primary aldosteronism (PA). However, despite being the gold-standard procedure, AVS protocols are not standardized and vary widely between centers. The objective of the present study was to assess whether the presence or absence of contralateral adrenal (CL) suppression has an impact on the postoperative clinical and biochemical parameters in patients who underwent unilateral adrenalectomy for PA. Design and method: The study was retrospectively carried out in eight referral hypertension centers in Italy, Germany and Japan. Case detection and subtype differentiation were performed according to the Japan Endocrine Society and The Endocrine Society guidelines and a total of 234 AVS procedures were included in the study. CL suppression was defined as aldosterone/cortisol non dominant adrenal vein/aldosterone/cortisol peripheral vein less than 1. Results: Overall, 82% of patients displayed CL suppression at AVS, with no statistically significant differences among centers. This percentage was significantly higher in ACTH-stimulated compared with basal procedures (90% vs 77%). The contralateral ratio was inversely correlated with the aldosterone level at diagnosis and, among AVS parameters, with the lateralization index (P < 0.02 and P < 0.01, respectively). To investigate whether the presence of CL suppression was correlated with response to adrenalectomy, we analyzed the CL suppression status with regard to the patient's clinical and biochemical postoperative parameters. No differences were observed between the two groups for the main clinical and biochemical parameters (systolic and diastolic blood pressure, aldosterone, PRA, PRC, K+, number of drugs, reduction of blood pressure levels, and the number of classes of drugs assumed), but patients with CL suppression underwent a significantly larger reduction in aldosterone levels after adrenalectomy. Conclusions: For patients with lateralization indices of greater than 4 (which comprised the great majority of subjects in this study), contralateral suppression should not be required to refer patients to adrenalectomy because it is not associated with a larger blood pressure reduction and might exclude patients from curative surgery.